Lithography of Aluminum Coated PVDF Annular Array for Photoacoustic Endoscopy (Communications in Computational Physics, 2018)
Focused transducers are frequently used in photoacoustic endoscopy (PAE)to ensure high acoustic resolution beyond the depth of optical diffraction. Althoughmost transducers in PAE are ceramic and focus-fixed, we here propose the polyvinylidinefluoride (PVDF) based annular array to reduce the fabrication cost, and to allowdynamic focusing for increased depth of field. In this work, a method of direct lithographyon the aluminum coated PVDF films was used for the annular array fabrication.The PVDF annular array was built with a 110 µm thick aluminum coated PVDF film,which contained three independent rings of equal width within a 5.5 mm aperturesize. Phantom experiments were conducted for field test, and a simple linear modelwas used to compare the acquired results in the acoustic field test. The device wasused for demonstration in PAE application. Potential applications of the proposedmethod include the PAE imaging of several large human organs and lumens such asthe gastrointestinal tract and the cervical canal.
Keywords: Polyvinylidine fluoride; annular array; photoacoustic endoscopy; mask-and-etch method.